PENGARUH PENERAPAN HANDOUT BERMUATAN KECERDASAN KOMPREHENSIF MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KOMPETENSI FISIKA SISWA DI SMAN 1 - Rahma Fikri Nuradi; Mahrizal Mahrizal; Zulhendri Kamus (Universitas Negeri Padang, 2016)
This research is conducted because of the low competence of Physics students. One of factor causes this problem that the using of learning materials, have not contributed to achieve all competencies namely knowledge, spiritual attitudes, social attitudes, and skills. The purpose of research is to determine the effect of applying a comprehensive intelligence handout in inquiry learning model to improve the competence of Physics students at SMAN 1 Padang. The type research is a quasi-experimental (Quasi Experiment) with Randomized Control Group Only Design. The population was all students of class X MIA SMAN 1 Padang enrolled in the Academic Year 2015/2016. Sampling was done by cluster random sampling. Samples were class X MIA1 as an experimental class and class X MIA 9 as the control class. The data include knowledge, spiritual attitudes, social attitudes, and skills competences. The research instrument are achievement test for knowledge, observation sheet spiritual attitudes and social attitudes, and the rubric for the skill. Data analyzed using (t test) with significant 0.05. The results of research is that